If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(a + -4) = 3a + 2 Reorder the terms: 5(-4 + a) = 3a + 2 (-4 * 5 + a * 5) = 3a + 2 (-20 + 5a) = 3a + 2 Reorder the terms: -20 + 5a = 2 + 3a Solving -20 + 5a = 2 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -20 + 5a + -3a = 2 + 3a + -3a Combine like terms: 5a + -3a = 2a -20 + 2a = 2 + 3a + -3a Combine like terms: 3a + -3a = 0 -20 + 2a = 2 + 0 -20 + 2a = 2 Add '20' to each side of the equation. -20 + 20 + 2a = 2 + 20 Combine like terms: -20 + 20 = 0 0 + 2a = 2 + 20 2a = 2 + 20 Combine like terms: 2 + 20 = 22 2a = 22 Divide each side by '2'. a = 11 Simplifying a = 11
| 3=-6x+6x | | 25x-2=13 | | 36=c+5 | | -8x-94=77+x | | 10n-8=36 | | 144=3(5x+8) | | 3x-18=-63 | | -8+(-4)-(-3)+6-10= | | -3(-2n)=63 | | 3x+18/6x | | 3.5n=11n | | 23+18u=21+14u | | (x/2)+(3/4)=(7/4) | | 10x+(10500/x)+100=0 | | -3x+17+5x=11+2(x+3) | | (-3x^3+5x^2+11x)-(6x^2-11x+7)+(5x^3+7x-11)= | | a+14=bfora | | 6+9(x-12)= | | 126*47/63*1/4 | | 19-(4m+5)=5+3m-12 | | f(x)=15(-3)+4 | | 7/2+2x=13 | | 7(y-8)+24=2(y-6) | | -20=6(6x+5)+19x | | 40=200/x | | -97-2x=3x+48 | | 45x-8=12 | | 82=(3x+2)+x | | 13x+9+15x-1=180 | | f(x)=15(0)+4 | | 5m/2-30=5 | | x+16=yforx |